2018
DOI: 10.1177/0269881118798339
|View full text |Cite
|
Sign up to set email alerts
|

Acute ingestion of rosemary water: Evidence of cognitive and cerebrovascular effects in healthy adults

Abstract: Background: The use of herbal extracts and supplements to enhance health and wellbeing is increasing in western society. Aims: This study investigated the impact of the acute ingestion of a commercially available water containing an extract and hydrolat of rosemary (Rosmarinus officinalis L. syn. Salvia rosmarinus Schleid.). Aspects of cognitive functioning, mood and cerebrovascular response measured by nearinfrared spectroscopy provided the dependent variables. Methods: Eighty healthy adults were randomly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 91 publications
2
13
0
Order By: Relevance
“…The antidepressant properties have been studied in various models [ 7 , 8 ]; we have earlier shown that rosemary infusion has antidepressant/anxiolytic-like and anticholinesterase effects [ 9 ]. In 2018, an intervention study in healthy adults showed that rosemary water consumption had beneficial cognition effects, which agreed with those previously discovered for inhaling the scent of rosemary essential oil [ 10 ].…”
Section: Introductionsupporting
confidence: 81%
“…The antidepressant properties have been studied in various models [ 7 , 8 ]; we have earlier shown that rosemary infusion has antidepressant/anxiolytic-like and anticholinesterase effects [ 9 ]. In 2018, an intervention study in healthy adults showed that rosemary water consumption had beneficial cognition effects, which agreed with those previously discovered for inhaling the scent of rosemary essential oil [ 10 ].…”
Section: Introductionsupporting
confidence: 81%
“…Compared to no aroma controls they report peppermint as having a large impact that appears quickly and that is maintained for some time following the removal of the aroma. Although no measures of cognition were included in the study the changes reported for the haemodynamic measures coincide with those observed for oral administration of rosemary where associated improvements on cognition were also reported [27]. It may be therefore that improved cognitive performance is a consequence of increased delivery of glucose and oxygen at times of high demand.…”
Section: Discussionmentioning
confidence: 87%
“…These positive results were previously obtained with chronic supplementation in humans suffering from different diseases such as Alzheimer's disease or in patients with chronic fatigue syndrome ( 23 , 24 ). Acute Salvia supplementation was also beneficial in healthy individuals for mood, memory, or attention ( 7 , 9 11 , 25 ). More specifically, in healthy individuals, the two species of Salvia under investigation in the present study ( S. officinalis and S. lavandulaefolia ) have, separately, demonstrated improvements for immediate or delayed word recall, speed of memory, and Stroop test ( 7 , 10 , 26 ).…”
Section: Discussionmentioning
confidence: 99%